Nutritional, Phytochemical and Antioxidant Analyses of Bee Bread from Different Regions In Malaysia - Zaidatul Akmal, Othman; Mahaneem, Mohamed; Liza, Noordin; Norsuhana, Omar (2017)
Objective: To compare nutritional, phytochemical and antioxidant properties of bee bread from three different regions of Malaysia which include Kelantan (east coast region), Selangor (central region) and Perak (northern region), Malaysia. Methodology: Bee bread samples of stingless bee (Heterotrigona itama) were subjected for nutritional analysis using standard hydrolysis and oxidation methods. Phytochemical screening was carried out on aqueous and ethanol extracts of bee bread. Total phenolic and flavonoid contents, free radical scavenging activity and ferric reducing activity of the extracts were assessed using Folin-Ciocalteu method, aluminium chloride reaction, 2, 2-diphenyl-1- picrylhydrazyl (DPPH) assay and ferric reducing antioxidant power (FRAP) assay, respectively. Results: All samples had essential and non-essential amino acids, carbohydrates, proteins, fat, moisture, flavonoids, tannins, phenols, xanthoproteins, cardiac glycosides, terpenoids, saponins, resins, and antioxidant activities. Samples from Selangor had the highest content for alanine, glycine, isoleucine, total protein and total energy while samples from Perak had the highest content for fat and moisture. Ethanol extract had significantly higher antioxidant activities compared to aqueous extract with the highest total phenolic and flavonoid contents in samples from Perak and the highest free radical scavenging activity in samples from Selangor. Conclusion: Bee bread from Malaysia has good nutritional and antioxidant properties which may suggest its use as a dietary supplement. The differences of the compositions and antioxidant activities among the samples might be related to the geographical location.